Business Incubator To Development Students' Entrepreneurial Soul - Novita, Yulia; Ibrahim, Nelvia (Journal of Management, 2024)
Students as Agents of Change from an early age must have a broad understanding of the importance of progress in the business sector, including strengthening the entrepreneurial spirit. The cultivation of an entrepreneurial spirit must be supported by the concern of various parties, including the world of higher education. This will in turn give birth to independent entrepreneurs and MSME players who are imbued with the attitude and character of entrepreneurs who are ready to survive and develop the business world in the future. The various strategies used to produce entrepreneurs and MSMEs in higher education are very important to carry out systematically and continuously. This article aims: To provide an overview of strategies for creating an entrepreneurial spirit in students and their relationship to creating independent MSMEs. Providing suggestions and solutions to parties related to cultivating an entrepreneurial spirit in students can provide a basic support for the realization of independent MSMEs. This article concludes that there are several strategies used in creating an entrepreneurial spirit in students, namely by providing motivation and understanding related to entrepreneurial character, namely Action Oriented, simple thinking, Looking for new opportunities, Pursuing opportunities and high discipline, Taking the best opportunities, Focusing on execution, Focusing everyone's energy on the business they are involved in and real strategies that can be implemented in higher education, namely Achieving learning outcomes in the curriculum, Participating in Student Creativity Programs, Creating a Business incubator